Pengelolaan Alam Wonogiri pada Paruh Pertama Abad XX - Pradita, Dennys; Mustafa, Hanif Risa (Fakultas Ilmu Budaya Universitas Diponegoro, 2024)
Wonogiri in colonial period was part of the Mangkunegaran region. Wonogiri is known for its rich forests, but until the 19th century the region did not show much economic progress. This paper will discuss the early description of forests and nature in Wonogiri, the exploitation of nature and its impact on the environment. The purpose of this research is to see the process of changing Wonogiri's environment to economic purposes, especially in changing the image of the forest which has an economic impact on the community and the impact of environmental damage. This research uses the historical method. This research begins with the collection of sources. The sources used are mostly newspaper reports which are then compared with other reports and journal articles. The exploitation of nature in Wonogiri is basically divided into two, the first is to take direct results such as teak forests, and the second way is to convert forest land into plantations. On the other hand, the exploitation of nature in Wonogiri also has an impact on environmental damage. In the form of floods, landslides and wild animals that lose their food chain, causing conflict with humans.